Flouting of Grice’s Maxims in The Mitchells vs. The Machines Film - Ni Kadek Debi Puspita Manggalita; Desak Putu Eka Pratiwi; Putu Nur Ayomi (RETORIKA: Jurnal Ilmu Bahasa, 2022)
Obeying the cooperative principle is an important rule that must be done to attain a good and relevant conversation, which can be divided into four categories of maxims, such as maxim of quality, maxim of quantity, maxim of manner, and maxim of relation. However, in everyday life, there are still many people who flout these maxims which causes their conversation to be ineffective. This study aims to determine the types of flouting maxim found in The Mitchells vs. The Machines film is based on the Cooperative Principle theory of Grice (1975). This study also aims to analyze the reasons of flouting maxim committed by characters using Flouting Maxim Strategies theory from Cutting (2002) and Illocutionary Functions of Politeness theory from Leech (1983). The method used in this research is the descriptive qualitative method. The data were collected from the utterances of the characters that flout the maxims in the film through the observation method. The results showed that there were 45 cases of flouting maxim found in the film. The maxim that is flouted the most is the maxim of relation. There were several reasons the characters flouted the maxims. Related to strategies and functions, the most frequently used reasons are the strategy of being irrelevant and competitive function. This is because the characters tend to say things outside the topic being discussed with the intention of asking people to do something.